Impact of Left Atrial Posterior Wall Ablation During Pulsed-Field Ablation for Persistent Atrial Fibrillation - Turagam, Mohit K; Neuzil, Petr; Schmidt, Boris; Reichlin, Tobias; Neven, Kars; Metzner, Andreas; Hansen, Jim; Blaauw, Yuri; Maury, Philippe; Arentz, Thomas; Sommer, Philipp; Anic, Ante; et al. (JACC. Clinical electrophysiology, 2024)
BACKGROUND: Pulmonary vein isolation (PVI) alone is insufficient to treat many patients with persistent atrial fibrillation (PersAF). Adjunctive left atrial posterior wall (LAPW) ablation with thermal technologies has revealed lack of efficacy, perhaps limited by the difficulty in achieving lesion durability amid concerns of esophageal injury. OBJECTIVES: This study aims to compare the safety and effectiveness of PVI + LAPW ablation vs PVI in patients with PersAF using pulsed-field ablation (PFA). METHODS: In a retrospective analysis of the MANIFEST-PF (Multi-National Survey on the Methods, Efficacy, and Safety on the Post-approval Clinical Use of Pulsed Field Ablation) registry, we studied consecutive PersAF patients undergoing post-approval treatment with a pentaspline PFA catheter. The primary effectiveness outcome was freedom from any atrial arrhythmia of ≥30 seconds. Safety outcomes included the composite of acute and chronic major adverse events. RESULTS: Of the 547 patients with PersAF who underwent PFA, 131 (24%) received adjunctive LAPW ablation. Compared to PVI-alone, patients receiving adjunctive LAPW ablation were younger (65 vs 67 years of age, P = 0.08), had a lower CHA2DS2-VASc score (2.3 ± 1.6 vs 2.6 ± 1.6, P = 0.08), and were more likely to receive electroanatomical mapping (48.1% vs 39.0%, P = 0.07) and intracardiac echocardiography imaging (46.1% vs 17.1%, P < 0.001). The 1-year Kaplan-Meier estimate for freedom from atrial arrhythmias was not statistically different between groups in the full (PVI + LAPW: 66.4%; 95% CI: 57.6%-74.4% vs PVI: 73.1%; 95% CI: 68.5%-77.2%; P = 0.68) and propensity-matched cohorts (PVI + LAPW: 71.7% vs PVI: 68.5%; P = 0.34). There was also no significant difference in major adverse events between the groups (2.2% vs 1.4%, respectively, P = 0.51). CONCLUSIONS: In patients with PersAF undergoing PFA, as compared to PVI-alone, adjunctive LAPW ablation did not improve freedom from atrial arrhythmia at 12 months.
Keywords: výsledek terapie; Heart Atria; Male; retrospektivní studie; atrial fibrillation; Aged; pulmonary vein isolation; mužské pohlaví; senioři; registrace; Catheter Ablation; srdeční síně; Atrial Fibrillation; Pulmonary Veins; Treatment Outcome; lidé; ženské pohlaví; Humans; posterior wall ablation; pulsed field ablation; venae pulmonales; Registries; Retrospective Studies; katetrizační ablace; Female; lidé středního věku; fibrilace síní; Middle Aged